(untitled) (Research, Society and Development, 2021)
The herbal medicine has medicinal plants or their derivatives as input. Despite numerous benefits, indiscriminate use and failures during production can expose the end consumer to harmful effects on their health. In this sense, the study evaluated the physical-chemical and microbiological quality of plant inputs used in a municipal pharmacy in the southwestern region of Paraná. Samples of dry extracts from: Cymbopogon citratus, Baccharis trimera., Aesculus hippocastanum, Equisetum arvense, Echinodorus grandiflorus, Curcuma longa, Ginkgo biloba, Piper methysticum, Melissa officinalis and Passiflora incarnata were analyzed. For the physical-chemical evaluation, the tests were carried out, according to the Brazilian Pharmacopoeia (2019): organoleptic characteristics, humidity, granulometry, pH, density, solubility and secondary constituents, among which flavonoids, saponins and tannins. For the microbiological analysis, the presence of total microorganisms, molds, yeasts, Salmonella sp and Shiguella sp was determined, according to Barbosa (2014). The organoleptic evaluation revealed that all samples were presented with a fine and homogeneous powder aspect, with a characteristic odor and color of each species. The dry extracts showed results of moisture content, particle size, pH and density within the pharmacopoeic reference values. Regarding solubility, the E. arvense sample proved to be practically insoluble in the solvent used. All samples tested positive for the presence of flavonoids. The samples of G. biloba, P. methysticum and P. incarnata did not present saponins. No sample showed contamination by total bacteria, Salmonella sp and Shiguella sp. Therefore, the results obtained in this research meet the parameters of the current legislation, proving the quality of the studied extracts.